Hydrochemical Changes Before and After Earthquakes Based on Long‐Term Measurements of Multiple Parameters at Two Sites in Northern Iceland—A Review. Issue 3 (7th March 2019) - Skelton, A.; Liljedahl‐Claesson, L.; Wästeby, N.; Andrén, M.; Stockmann, G.; Sturkell, E.; Mörth, C.‐M.; Stefansson, A.; Tollefsen, E.; Siegmund, H.; Keller, N.; Kjartansdóttir, R.; et al.
Abstract: Hydrochemical changes before and after earthquakes have been reported for over 50 years. However, few reports provide sufficient data for an association to be verified statistically. Also, no mechanism has been proposed to explain why hydrochemical changes are observed far from earthquake foci where associated strains are small (<10 −8 ). Here we address these challenges based on time series of multiple hydrochemical parameters from two sites in northern Iceland. We report hydrochemical changes before and after M >5 earthquakes in 2002, 2012, and 2013. The longevity of the time series (10 and 16 years) permits statistical verification of coupling between hydrochemical changes and earthquakes. We used a Student t test to find significant hydrochemical changes and a binomial test to confirm association with earthquakes. Probable association was confirmed for preseismic changes based on five parameters (Na, Si, K, δ 18 O, and δ 2 H) and postseismic changes based on eight parameters (Ca, Na, Si, Cl, F, SO4, δ 18 O, and δ 2 H). Using concentration ratios and stable isotope values, we showed that (1) gradual preseismic changes were caused by source mixing, which resulted in a shift from equilibrium and triggered water‐rock interaction; (2) postseismic changes were caused by rapid source mixing; and (3) longer‐term hydrochemical changes were caused by source mixing and mineral growth. Because hydrochemical changes occur at small earthquake‐related strains, we attribute source mixing and water‐rock interaction to microscale fracturing. Because fracture density and size scale inversely, we infer that mixing of nearby sources and water‐rock interaction are feasible responses to small earthquake‐related strains. Plain Language Summary: Changes in groundwater chemistry before and after earthquakes have been reported for over 50 years. However, few studies have been able to prove that the earthquakes caused these changes. Also, no study has explained why these changes are often reported far from where the earthquake occurred. Here we address these challenges based on measurements of groundwater chemistry made at two sites in northern Iceland over time periods of 10 and 16 years. We used statistical methods to prove that the earthquakes caused changes of ground water chemistry both before and after the earthquakes. We showed that changes of groundwater chemistry before earthquakes were caused by slow mixing between different groundwaters, which triggered reactions with the wall rock that changed groundwater chemistry, and that changes of groundwater chemistry after earthquakes were causes by rapid mixing between different groundwaters. That these changes were detected far from where the earthquakes occurred suggests that cracking of the wall rock at a very small scale was all that was needed for mixing of different groundwaters and reactions with the wall rock to occur. Key Points: Hydrochemistry has been measured on a weekly basis at two sites for 10–16 years in northern Iceland Three M >5 earthquakes were preceded and/or followed by changes of groundwater chemistry at both sites Chemical changes occur far from earthquake foci at small strains and probably reflect source mixing and water‐rock interaction